The Influence Analysis Position on The Employee Performance of SMK PGRI Telagasari Karawang Regency - Fakhri Mujahid Maolani; Solehudin Solehudin (Jurnal Ilmiah Manajemen dan Bisnis, 2023)
This study aims to determine, analyze, and explain the effect of job analysis on the employee’s performance of SMK PGRI Telagasari Karawang. This research uses descriptive analysis and verification methods with a quantitative approach. The population in this study were users of SMK PGRI Telagasari Karawang Regency, the sample in this study was 85 respondents. The sampling technique used in this research is a saturated sample, namely taking respondents using the population as the research sample. The analysis technique used in this study is multiple linear regression analysis. The results showed that there was a significant effect of job analysis on employee performance at SMK PGRI Telagasari, Karawang Regency. The magnitude of the influence of job analysis on the performance of employees of SMK PGRI Telagasari Karawang Regency is 89.4%. While the remaining 10.6% is explained by other factors not examined in this study.